병렬 설치형 저압막 모듈 배관의 유량 균등 분배 평가에 관한 연구 - 장석현(SeokHyun Jang); 윤석민(Sukmin Yoon); 김시연(Si-Yeon Kim); 이영주(Young-Joo Lee); 박노석(No-Suk Park) (Daehan hwan'gyeong gonghag hoeji, 2021)
목적 : 본 연구에서는 실제 정수처리에 적용되고 있는 외압식 저압막(정밀여과막, Microfiltration) 여과 공정을 대상으로 각 모듈로 유입되는 유량의 균등 정도를 실측하고, 전산유체역학(Computational Fluid Dynamics, CFD)를 이용하여 그 원인을 밝히고자 하였다. 방법 : 본 연구에서는 막 모듈배관에서 각 모듈로 유입되는 유량을 측정하기 위해 이동형 초음파 유량계를 사용하였으며, 이를 검증하기 위해 전산유체역학 기법을 이용하였다. 결과 및 토의 : 초음파 유량계를 이용한 실측과 CFD 모사 결과로부터 헤더 배관 끝단에 위치한 분지관으로부터의유출 유량이 유입구 근처의 분지관 유량보다 3배 높았다. 그 이유는 각 막 모듈 사이에서 발생하는 차압이 헤더파이프 끝으로 갈수록 더 높았기 때문이다. 결론 : 지관의 단면적의 합과 헤더 배관의 통수 단면적의 비를 약 80배 정도 감소할 경우 각 분지관에서 막 모듈로유입되는 유량이 거의 균등한 것을 확인 할 수 있었다. 또한 관내 흐름이 천이류 및 층류인 경우(Reynolds No.가대략 4,000이하) 각 분지관에서 막 모듈로 유입되는 유량을 균등화 시킬 수 있을 것으로 판단할 수 있다. Objectives : In this study, the degree of uniformity of the flow rate flowing into each module is measured for the external pressure typed low-pressure membrane (microfiltration) filtration process that has been actually applied to water treatment, and computational fluid dynamics (CFD) technique is used to clarify the cause and effect. Methods : Mobile ultrasonic flow meter was used to measure the flow rate flowing from the membrane module pipe to each module, and the CFD technique was used to verify this. Results and Discussion : From the results of the actual measurement using ultrasonic flowmeter and CFD simulation, it was confirmed that the outflow flow rate from the branch pipe located at the end of the header pipe was three times higher than that of the branch pipe near the inlet. The reason was that the differential pressure generated between each membrane module was higher toward the end of the header pipe. Conclusions : When the ratio of the sum of the cross-sectional area of the branch pipe and the cross-sectional area of the header pipe was reduced by about 30 times, it was confirmed that the flow rate flowing from each branch pipe to the membrane module was almost equal. Also, If the flow in the header pipe is transitional or laminar (Reynolds No. is approximately 4,000 or less), the flowrate flowing from each branch pipe to the membrane module can be more even. KCI Citation Count: 0